Perkembangan Uji Stabilitas Berdasarkan Parameter pada Sediaan Suspensi dengan Berbagai Bahan Aktif yang Berbeda - Salman Salman; Asri Yuniar Dwi Nanda; Diva Afiah Hanifa Irawan; Najla Yusiana Wahyudi; Nolla Olipia Elva Megrian (Journal of Pharmaceutical and Sciences, 2023)
Stability test is one of the things that needs to be done on pharmaceutical preparations, stability tests need to be done before the product is produced by a manufacturer, whether production on an industrial scale or not on an industrial scale. The development of liquid preparations is currently very rapid, one of which is suspension. Suspension is a liquid preparation containing insoluble solid particles dispersed in the liquid phase. The stability of suspension preparations was evaluated by carrying out organoleptic tests, volume sedimentation, re-dispersion, viscosity density, particle size distribution, and pH measurements. The development of stability tests on suspension preparations from year to year does not show many different changes. In early 1992, only three non-specific test parameters were carried out: drug concentration, pH, and microbial growth. Meanwhile, for the difference in the 2017 journal, an acceleration stability test was carried out, which observed sedimentation volume, flow time, particle size, viscosity, and redispersibility. Parameter assays have become more specific and have been modified over the years to ensure the stability of pharmaceutical suspensions is thoroughly evaluated